Addition of Dexamethasone and Buprenorphine to Bupivacaine Sciatic Nerve Block. Issue 4 (July 2015) - YaDeau, Jacques T.; Paroli, Leonardo; Fields, Kara G.; Kahn, Richard L.; LaSala, Vincent R.; Jules-Elysee, Kethy M.; Kim, David H.; Haskins, Stephen C.; Hedden, Jacob; Goon, Amanda; Roberts, Matthew M.; Levine, David S.
<x xml:space="preserve">Abstract</x> Background and Objectives Sciatic nerve block provides analgesia after foot and ankle surgery, but block duration may be insufficient. We hypothesized that perineural dexamethasone and buprenorphine would reduce pain scores at 24 hours. Methods Ninety patients received ultrasound-guided sciatic (25 mL 0.25% bupivacaine) and adductor canal (10 mL 0.25% bupivacaine) blockade, with random assignment into 3 groups (30 patients per group): control blocks + intravenous (IV) dexamethasone (4 mg) (control); control blocks + IV buprenorphine (150 μg) + IV dexamethasone (IV buprenorphine); and nerve blocks containing buprenorphine + dexamethasone (perineural). Patients received mepivacaine neuraxial anesthesia and postoperative oxycodone/acetaminophen, meloxicam, pregabalin, and ondansetron. Patients and assessors were blinded to group assignment. The primary outcome was pain with movement at 24 hours. Results There was no difference in pain with movement at 24 hours (median score, 0). However, the perineural group had longer block duration versus control (45.6 vs 30.0 hours). Perineural patients had lower scores for "worst pain" versus control (median, 0 vs 2). Both IV buprenorphine and perineural groups were less likely to use opioids on the day after surgery versus control (28.6%, 28.6%, and 60.7%, respectively). Nausea after IV buprenorphine (but not perineural buprenorphine) was severe, frequent, and bothersome. Conclusions Pain scores were very low at 24 hours after surgery in the context of multimodal analgesia and were not improved by additives. However, perineural buprenorphine and dexamethasone prolonged block duration, reduced the worst pain experienced, and reduced opioid use. Intravenous buprenorphine caused troubling nausea and vomiting. Future research is needed to confirm and extend these observations.